Makna Ritual Budaya Pertanian Yang Berkaitan Dengan Leksikon Bidang Persawahan Pada Masyarakat Bali - Ida Ayu Putu Aridawati (Jayapangus Press, 2020)
The meaning and cultural value ​​associated with Balinese local wisdom in the field of rice fields are related to agricultural ritual activities in the field of rice fields. The problem discussed in this study is how the reflection of cultural values ​​in relation between religious ceremonies and the agricultural lexicon in the fields of traditional farming communities in Bali, which include: the meaning of rituals during pre-rice planting, rice planting period, and post-rice planting.This study aimed to obtain complete description of the ritual meaning of the pre-rice planting, rice planting period, and post-rice planting . The theory which is used as the basis for the discussion process is ecolinguistic theory. In collecting data the methods of observation, interview and questionnaire are used. This method is supported by note taking, recording, and documentation. In data analysis quantitative and qualitative methods are used. In presenting the results of data analysis used formal and informal methods, delivered with inductive and deductive techniques. Based on data analysis, the results of the agricultural lexicon of rice fields included three stages, namely (1) pre-planting, such as: mapag toya 'fetching water', marekang toya 'obtained water', ngendagin ‘start working in the fields’, and ngurit ‘sowing’; (2) planting period, including: pangawiwit ‘a place to start’, and nandur 'planting rice'; (3) the post-planting period, including: mubuhin 'offering porridge', mabahin 'fruit bearing rice', ngiseh / biyakukung 'pregnant rice', ngulapin 'cleaning', neduh, penulak paksi ‘bird repellent’, penulak bikul ‘rat repellent’, penulak walang sangit ‘repellent riceear bug’, candang, lanas, and mati muncuk ‘the tip of the rice leaf found dead’, ngusaba, nyangket ‘cutting rice’, magurupiduka ‘beg for forgiveness’, and mantenin ‘presenting offerings’.